Pertumbuhan biak kalus dan suspensi sel tanaman kina (Cinchona ledgeriana Moens) Growth of callus and cell suspension cultures of cinchona (Cinchona ledgeriana Moens) - . SUMARYONO; Imron RIYADI (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2005)
SummaryIn vitro technology of plants can be used topropagate plants and to produce secondarymetabolites with a short and continuousproduction cycle. Callus cultures of cinchona(Cinchona ledgeriana Moens) on solid media andcell cultures in liquid media have beenestablished. Callus could be easily initiated fromvarious explants of cinchona clone CB5, GA22and QRC312. The best callus initiation andproliferation were obtained on a Woody Plant(WP) solid medium supplemented with 15 µMpicloram,0.5 µM BAP and 1 µM phloroglucinol.In this medium the fresh weight of callusincreased by 12 to 14-fold within 5 to 6 weeks.Callus that constantly grew fast was selected as amaterial source for cell suspension cultures. InWP liquid medium with the same composition,the cells remained to grow fast where cell volumeafter sedimentation (CVS) increased by almost4-fold in two weeks. However, repeated sub-cultures decreased cell growth rate. The cellsuspension culture was then scaled-up in a 5-Lbioreactor. The culture medium was the same asin Erlenmeyer flasks. Cells in a bioreactor grewvery slowly, the cell biomass fresh weight andpacked cell volume (PCV) increased by 34% and50% respectively after 21 days of culture,although most of the cells remained viable.RingkasanTeknologi in vitro tanaman dapat digunakanuntuk memperbanyak tanaman dan memproduksisenyawa sekunder dengan siklus sangat singkatdan berkelanjutan. Biak kalus tanaman kina(Cinchona ledgeriana Moens) pada mediumpadat dan biak sel di medium cair telahdikembangkan. Kalus dengan mudah dapatdiinduksi dari berbagai jenis eksplan tanamankina klon CB5, GA22 dan QRC312. Inisiasi danproliferasi kalus terbaik diperoleh pada mediaWoody Plant (WP) padat dengan pikloram 15µM, BAP 0,5 µM dan floroglusinol 1 µM. Padamedium ini bobot basah kalus meningkat 12-14kali lipat dalam waktu 5-6 minggu. Kalus yangtetap tumbuh cepat dipilih sebagai sumber bahanuntuk biak suspensi sel. Dalam medium cair WPdengan komposisi yang sama, sel tetap tumbuhdengan pesat, volume sel setelah pengendapan(CVS) meningkat hampir empat kali lipat dalamwaktu dua minggu. Namun subkultur berulangmenurunkan laju pertumbuhan sel. Skala biaksuspensi sel kemudian diperbesar dalam bio-reaktor kapasitas 5 L. Medium kultur yangdigunakan sama dengan medium pada labuErlenmeyer. Pertumbuhan sel dalam bioreaktorsangat lambat, bobot basah sel dan packed cellvolume (PCV) hanya bertambah berturut-turutsebesar 34% dan 50% setelah 21 hari dalamkultur, walaupun sebagian besar sel tetap viabel.